Dampak Demokrasi terhadap Integrasi Pemilu dan Kampanye Digital dalam Pilkada Garut - Muslim, Jaliludin; Nurjaman, Daffa Syafiq (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
This study examines the role of digital campaigns in the Pilkada Garut, focusing on their impact on electoral integrity and democratic participation. Utilizing a qualitative descriptive-analytic approach, the research analyzes how digital campaigns influence voter behavior and election transparency. Data collection involved bibliometric analysis using Google Scholar and VOSViewer to identify trends in digital campaigns, electoral integrity, and democracy literature, alongside content analysis of relevant articles and reports. Additionally, in-depth interviews with four voters from various Garut districts provided primary insights. Findings reveal that digital campaigns effectively mobilize voters, particularly youth, through targeted social media messaging. However, challenges such as misinformation and unequal access to technology threaten electoral integrity and equitable participation. The study concludes that while digital campaigns can enhance democracy by increasing voter engagement, strategies must ensure equitable information access and mitigate digital misinformation risks. Recommendations include enhancing digital literacy, improving digital infrastructure in remote areas, and fostering collaboration with social media platforms to protect electoral integrity.